Formação continuada de professores (as) da educação infantil da rede municipal de ensino de Alegrete/RS: perspectivas da qualidade das práticas pedagógicas - Vargas, Elizete Borges (2022)
This project, developed in the Research Line Policies and Management of Basic and Higher Education, of the Postgraduate Program in Public Policies and Educational Management, of the Federal University of Santa Maria (UFSM-RS), addresses the theme Continuing Education of Early Childhood Education Teachers in the Municipal Education Network of Alegrete/RS: Perspectives on the Quality of Pedagogical Practices. It was intended, as a general objective, to analyze the relevance and impacts on the effectiveness of the pedagogical work of continuing education offered in the municipal education network of Alegrete/RS. As specific objectives, to know and analyze the Continuing Education programs offered to Preschool Education teachers by the Municipal Department of Education; to understand in which way the selection criteria of the Continuing Education programs that the educational system of the city of Alegrete, RS, offered to the professionals of Early Childhood Education were implemented; to evaluate the possible impacts of the Continuing Education programs on the pedagogical work of Early Childhood Education teachers and, finally, to elaborate the Final Product, based on the methodology of a qualitative approach, of the Case Study and bibliographic type, whose municipal network served as a field of acting. The techniques were used for the elaboration and realization of questionnaires, directed to the research subjects, preschool teachers of the municipal education system and representatives of the Secretariat of Education, Culture, Sports and Leisure of Alegrete/RS (SECEL). The theoretical reference is organized based on the legislation of the Law of Directives and Bases of Education - LDB (9.394/96), National Common Curricular Base (2018) and on authors, such as Oliveira (2002;2008), Kramer (1999), Campos (1999) and, in the methodology, Gil (2002), among others. To analyze the constructed data, Bardin's (1977). The results pointed that most participants understood that the training courses were not relevant and did not produce significant impacts on their practices, due to the inadequacy of the themes for the reality of Early Childhood Education. As a final product, a guiding document was constructed with suggestions for SECEL (Secretariat of Education, Culture, Sports and Leisure ) regarding formative moments about the conception of childhood, reinforcing the importance of the Continuing Education process. Thus, through initiatives of this nature, it is possible to obtain a space for discussion, reflection and awareness for educators in general, the purpose of the theme addressed in this research.